Factors influencing consumers’ continuous purchase intention on fresh food e-commerce platforms: An organic foods-centric empirical investigation - Lin, Jiabao; Li, Ting; Guo, Jinyuan (Electronic commerce research and applications, 2021)
•How do e-commerce platform characteristics and organic foods characteristics affect continuous purchase intention?•The stimulus-organism-response (SOR) paradigm and perceived value drive research model.•Perceived value plays positive mediating role in the positive effects of e-commerce platform characteristics and organic foods characteristics on continuous purchase intention.•There are gender differences in the factors affecting continuous purchase intention towards organic foods. E-commerce has brought new opportunities to expand sales channels for fresh products. However, China’s fresh food e-commerce platforms currently have a low repurchase rate among consumers and face operating losses or bankruptcy. Therefore, from the perspective of perceived value, this research took organic foods as the research object and included gender differences, thereby establishing a theoretical model to explain the factors affecting consumers’ continuous purchase intention on fresh food e-commerce platforms. We surveyed consumers who bought organic foods online and collected 454 valid samples. First, the findings have shown that product characteristics (nutritional content, natural content, and ecological wealth) and platform characteristics (information quality, system quality, and service quality) significantly impact the perceived utilitarian value and perceived hedonic value of consumers. Second, perceived value plays a critical mediating role in influencing product characteristics and platform characteristics on consumers’ continuous purchase intention. Finally, the results suggest that enterprises should focus on product characteristics and platform characteristics to enhance consumers’ perceived value, thus increasing their continuous purchase intention.